Pengembangan Aplikasi Absensi Mobile Terintegrasi dengan Sistem Backoffice Berbasis Web Menggunakan Metode Pengembangan Perangkat Lunak Waterfall - Nasya Putri Restyarna; Andi Taufik; Eko Setia Budi (Journal of Informatics, Electrical and Electronics Engineering, 2025)
Attendance systems play a crucial role in human resource management by serving as the foundation for accurate and efficient employee presence tracking. PT Urun Bangun Negeri previously used a manual attendance method that was prone to data errors, manipulation, and inefficiencies in reporting. This study aims to develop a digital attendance application based on Android that integrates with a web-based backoffice system. The software development method used is the Waterfall model, consisting of requirement analysis, system design, implementation, and testing phases. Kotlin was used to develop the mobile application, while Laravel was used for the web system. Key features include GPS-based location validation and selfie verification for attendance authenticity. System testing using Blackbox and User Acceptance Test (UAT) methods showed that the application performed well, with a success rate of more than 95% and a very high level of user satisfaction. These results demonstrate that the developed system effectively enhances efficiency, accuracy, and transparency in the company’s attendance process.